A compacted non-pump self-circulation spray cooling system based on dual synthetic jet referring to the principle of two-phase loop thermosyphon. (15th January 2023) - Luo, Zhenbing; He, Wei; Deng, Xiong; Zheng, Mu; Gao, Tianxiang; Li, Shiqing
Abstract: A traditional spray cooling system usually requires a pump to circulate the fluid, and the kinetic energy of high-temperature steam is wasted. A two-phase loop thermosyphon (TPLT) which can circulate its working fluid is thermally driven. However, heat leakage may occur for low heating power. This paper proposes a compacted non-pump self-circulation spray cooling system named active two-phase loop thermosyphon (ATPLT). Dual synthetic jet integrated with spray cooling (DSJS) is used to enhance the performance of evaporator of ATPLT. Without an external pump, the waste heat and evaporation of liquid spray drive the system internal pressure to increase, which pumps the water to the reservoir as well as avoid heat leakage. It only needs a little working fluid and a little energy consumption for actuator, but can maintain hundreds of Watts of heat dissipation capability for a long time, which can facilitate the development of the energy systems. The performance of ATPLT is studied through temperature, pressure, laser particle size and particle image velocimetry experimental researches. The experimental results show that the cooling capability of ATPLT is mainly influenced by Re, We and Ja, and finally a correlation for ATPLT cooling is established with relative errors within ±18%. Highlights: A closed non-pump spray cooling system was designed. The flow characteristics under different micropore diameters were obtained. The spray droplet diameter distributions were obtained. The circulation modes under different heating power were summarized. A correlation for ATPLT cooling was established.